2013
DOI: 10.2903/j.efsa.2013.3144
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on the re‐evaluation of sodium stearoyl‐2‐lactylate (E 481) and calcium stearoyl‐2‐lactylate (E 482) as food additives

Abstract: Following a request by the European Commission, the Panel of Food Additives and Nutrient Sources added to Food (ANS) was asked to deliver a scientific opinion on the safety of sodium stearoyl-2-lactylate (E 481, SSL) and calcium stearoyl-2-lactylate (E 482, CSL) when used as food additives. SSL and CSL are used as emulsifiers and stabilizers. An Acceptable Daily Intake (ADI) of 20 mg/kg bw/day for SSL and CSL (either singly or in combination) was established in 1974 by the Joint FAO/WHO Expert Committee on Foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 16 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…Calcium stearoyl-2 lactylate is a white or slightly yellowish powder which is widely used in the bakery and dessert industry for food emulsification and stabilization. Commercially, CSL is produced by the esterification process of stearic acid with lactic acid and thereafter it is neutralized to the calcium salts [12,13]. Recently, several studies were conducted with sodium stearoyl-2-lactylate, which is similar with CSL, to evaluate growth performance and nutrient digestibility in broiler chickens [6,14].…”
Section: Introductionmentioning
confidence: 99%
“…Calcium stearoyl-2 lactylate is a white or slightly yellowish powder which is widely used in the bakery and dessert industry for food emulsification and stabilization. Commercially, CSL is produced by the esterification process of stearic acid with lactic acid and thereafter it is neutralized to the calcium salts [12,13]. Recently, several studies were conducted with sodium stearoyl-2-lactylate, which is similar with CSL, to evaluate growth performance and nutrient digestibility in broiler chickens [6,14].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, previous studies showed that low-energy content diet decreased the DM digestibility in broilers (Cho and Kim, 2013). This discrepancy in results could be due to different types of fat, and the strain and age of broilers (Ding et al, 2003).…”
Section: Effect Of Energy Contentmentioning
confidence: 74%